Comparative Analysis of Length of Stay and Inpatient Costs for Orthopedic Surgery Patients Treated with IV Acetaminophen and IV Opioids vs. IV Opioids Alone for Post-Operative Pain. Issue 9 (September 2016) - Hansen, Ryan; Pham, An; Strassels, Scott; Balaban, Stela; Wan, George
Abstract Introduction Recovery from orthopedic surgery is oriented towards restoring functional health outcomes while reducing hospital length of stay (LOS) and medical expenditures. Optimal pain management is a key to reaching these objectives. We sought to compare orthopedic surgery patients who received combination intravenous (IV) acetaminophen and IV opioid analgesia to those who received IV opioids alone and compared the two groups on LOS and hospitalization costs. Methods We performed a retrospective analysis of the Premier Database (Premier, Inc.; between January 2009 and June 2015) comparing orthopedic surgery patients who received post-operative pain management with combination IV acetaminophen and IV opioids to those who received only IV opioids starting on the day of surgery and continuing up to the second post-operative day. The quarterly rate of IV acetaminophen use for all hospitalizations by hospital served as the instrumental variable in two-stage least squares regressions controlling for patient and hospital covariates to compare the LOS and hospitalization costs of IV acetaminophen recipients to opioid monotherapy patients. Results We identified 4, 85, 895 orthopedic surgery patients with 1, 74, 805 (36%) who had received IV acetaminophen. Study subjects averaged 64 years of age and were predominantly non-Hispanic Caucasians (78%) and female (58%). The mean unadjusted LOS for IV acetaminophen patients was 3.2 days [standard deviation (SD) 2.6] compared to 3.9 days (SD 3.9) with only IV opioids (P < 0.0001). Average unadjusted hospitalization costs were 19, 024.9 (SD 13, 113.7) for IV acetaminophen patients and 19, 927.6 (SD 19, 578.8) for IV opioid patients (P < 0.0001). These differences remained statistically significant in our instrumental variable models, with IV acetaminophen associated with 0.51 days shorter hospitalization [95% confidence interval (CI) −0.58 to −0.44, P < 0.0001] and 634.8 lower hospitalization costs (95% CI −1032.5 to −237.1, P = 0.0018). Conclusion Compared to opioids alone, managing post-orthopedic surgery pain with the addition of IV acetaminophen is associated with shorter LOS and decreased hospitalization costs. Funding Mallinckrodt Pharmaceuticals.